HUMAN AND ANIMAL RELATIONSHIP IN AMERICAN HUSBANDRY SYSTEM PORTRAYED THROUGH E.B. WHITE’S CHARLOTTE’S WEB (1952) - Syahruni Junaid (Universitas Sam Ratulangi, 2025)
This research examines the representation of animal protection in E.B. White's novel “Charlotte's Web”, published in 1952, in the legal and social context of 20th century America. Using sociology of literature approach, this study analyzes characters such as Fern, Wilbur, Mr. Arable, and Mr. Zuckerman to illustrate the dynamics between humans and animals and the challenges faced by animals in the farming system. The research also connects the development of animal protection laws at the time with the characters' representations in the novel, as well as how literary works can reflect and influence social views on animals. The findings show that the characters in “Charlotte's Web” not only reflect animal protection issues, but also illustrate the changing ideologies and practices of animal husbandry that affect animal welfare. This research provides insight into the evolution of thinking about animal protection in America and the contribution of literature in shaping social consciousness